Histopathological analysis of the liver in hypercholesterolemia rats treated with Dillenia serrata fruits - Tien; Tri Wistya Utami; Pranita Aritrina; Laode Kardin; Sukurni; Andi Noor Kholidha Syarifin (Acta Biochimica Indonesiana, 2022)
Background: Dillenia serrata (locally known as singi) is a natural product with the potential to improve liver function in hypercholesterolemia, due to anticholesterol and antioxidant properties. Objective: This study aimed to investigate the effect of D. serrata on the histopathological features of rat livers induced by a high-fat diet. Methods: This study used a quasi-experimental in vivo with a post-test-only control group design. Rats were divided into four groups: normal, high-fat diet, as well as D. serrata, and simvastatin treatment. Hypercholesterolemia was induced by a high-fat diet for two weeks. Rat liver tissues were analyzed histologically using Hematoxylin-Eosin (HE) staining, and were observed under a light microscope at 40x magnification in five wide fields of view. Results: The high-fat diet group had the most adipose cells, while the D. serrata group had the least. Statistical analysis demonstrated a significant difference between the high-fat diet group and the other groups (p < 0.05). Interestingly, no significant difference between the D. serrata group and either the normal or simvastatin group (p > 0.05), suggesting the treatment of fruit may restore liver function comparable to normal and simvastatin group. Conclusion: The D. serrata fruit reduces the number of fat cells in the histopathology of rats induced with the high-fat diet.